International inequality in subjective well-being: An exploration with the Gallup World Poll - Pablo Gluzmann; Leonardo C. Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2017)
In this paper we compute inequality measures over the distribution of a subjective well-being variable constructed from a life satisfaction question included in the Gallup World Poll in almost all countries in the world. We argue that inequality in subjective well-being may be a better proxy for the degree of unfairness in a society than income inequality. We find evidence that inequality in subjective well-being has an inverse-U relationship with per capita GDP, but it is monotonically decreasing with respect to mean subjective well-being. We argue that this difference might be associated to inequality aversion in the space of utility.
Keywords: I31; D31; D39; D63; 330; inequality; subjective well-being; Kuznets curve; Gallup World Poll